2007
DOI: 10.1074/jbc.m704141200
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Is Overexpressed in Esophageal Squamous Cell Carcinoma and Promotes Tumorigenicity through β-Catenin-T-cell Factor/Lef Signaling

Abstract: Connective tissue growth factor (CTGF or CCN2), a member of the CCN family, is involved in diverse biological processes such as cell adhesion, proliferation, and angiogenesis. In this study, we show that overexpression of CTGF occurred in a significant proportion of esophageal squamous cell carcinoma (ESCC) samples that were of a high tumor grade and metastatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 44 publications
4
108
0
Order By: Relevance
“…CTGF can directly bind to cell surface integrin complexes thus activating ILK signaling (13,14). CTGF can also directly bind to LRP5/6, coreceptors of Wnt (15,16). Activation of ILK and LRP5/6 can lead to nuclear translocation of β-catenin and subsequent activation of target gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTGF can directly bind to cell surface integrin complexes thus activating ILK signaling (13,14). CTGF can also directly bind to LRP5/6, coreceptors of Wnt (15,16). Activation of ILK and LRP5/6 can lead to nuclear translocation of β-catenin and subsequent activation of target gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have also found that CTGFinduced lung pathology is associated with activation of β-catenin signaling, whereas treatment with CTGF antibody inhibits hyperoxia-activated β-catenin signaling. It is known that CTGF can activate β-catenin signaling by binding to cell surface integrins and lipoprotein receptor-related protein (LRP) 5/6, coreceptors of wingless/Int (Wnt) (13)(14)(15)(16). It is unknown, however, whether activation of β-catenin signaling mediates CTGF-induced alveolar and vascular pathology in neonatal mice.…”
Section: Introductionmentioning
confidence: 97%
“…The primer pairs used for real-time PCR are as follows: ephrinA5: F: 5 0 -GCAATCCCAGATAATGGAAGAA-3 0 , R: 5 0 -TCGGCT GACTCATGTACGGT-3 0 ; EGFR: F: 5 0 -CGGGACATAGT CAGCAGTG-3 0 , R: 5 0 -GCTGGGCACAGATGATTTTG-3 0 ; b-actin: F: 5 0 -GATCATTGCTCCTCCTGAGC-3 0 , R: 5 0 -ACTCCTGCTTGCTGATCCAC-3 0 . Amplification reactions were performed as described earlier (Deng et al, 2007).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Briefly, triplicate plates of cells were trypsinized and stained with Trypan blue, and unstained cells were counted using a haemocytometer. Colony-survival assay was performed as previously described 46 . Briefly, cells were seeded sparsely (2,000 cells per well for 6-well plates, 1,000 cells per well for 12-well plates) and were grown for 10 days with normal medium.…”
Section: Methodsmentioning
confidence: 99%